Evaluasi Efektivitas Penggunaan Antivirus Pada Pasien Covid-19 di Ruang Rawat Inap RSUD Dr. Moewardi - Andriani Noerlita (Fakultas Sains, Teknologi dan Kesehatan Universitas Sahid Surakarta, 2025)
This study aims to evaluate the effectiveness of using the antiviral drugs Remdesivir and Favipiravir in COVID-19 patients undergoing treatment at Dr. Moewardi General Hospital in Surakarta. The study utilizes a descrptive design with a retrospective data analysis approach involving 17 confirmed COVID-19 patients. The data analyzed includes patient profile, the severity of the disease, the typy of antiviral administered, and changes in clinical parameters such as creatinin levels, oxygen saturation (SpO2) and respiratory rate (RR). The results indicate that the majority of patients treated were male (88,33%) and over 50 years old (88,3%) with the most patients having a moderate severity level of the disease (58,9%0. Remdesivir was the most commonly used antiviral (76,4%). The use of Remdesivir was associated with an average increase in SpO2 of 4,15% and an increase in RR of 0,52 breaths/minute. On the other hand, the use of Favipiravir did not show a significant change in SpO2 but resulted in an increase in RR by 2,67 breath/minute. The use of combination antivirals showed the highest increase in RR of 7 breaths/minute. The study concludes that Remdesivir is more effective than Favipiravir in improving patient oxygenation without causing a significant increase in RR. However the use of antivirals, especially ini combination, requires close monitoring to prevent potential side effects. The results of this study are expected to provide guidance in selecting the most appropriate antiviral therapy for COVID-19 patients and emphasize the importance of intensive clinical monitoring during treatment.